Simulation of roof solar chimney for vertical axis wind turbine - Zarchi, Farzad Ramesh (2013)
Due to the important role of the renewable and sustainable energy sources in energy sector, a lot of efforts are made to reduce fossil fuel consumption. One option in small scale energy generation is roof solar chimney. Among many factors that affect the performance of a roof solar chimney is the angle of sun radiation which is an important factor that varies with different locations. It is crucial to find the optimum angle that a solar absorber should face the sun beams to absorb as much as solar energy as possible and get to its highest temperature possible. A location between 35o to 45o latitude is selected to simulate its climatic condition. The results show that an inclination of 30o from horizon seems to be a perfect choice for solar absorbers. An increase in geometry is necessary to get the required velocity output of the outlet opening of the solar chimney to power up a vertical axis wind turbine (VAWT). At least 3m/s of wind speed is required for the wind turbine (VAWT) with the rotor diameter of 1 meter. Final radius of the solar chimney to satisfy the need was about 4 meters.